1994
DOI: 10.1111/j.1365-2273.1994.tb01232.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective analysis of incidental paranasal sinus abnormalities on CT head scans

Abstract: A prospective analysis of the incidence of paranasal sinus opacification in 100 patients referred for cranial computerized tomography (CT) for non-sinus related problems is described. The findings were correlated with symptomatic assessment. Twenty-seven per cent of asymptomatic patients had sinus opacification. The study illustrates the importance of careful clinical correlation when interpreting CT scans of the paranasal sinuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 4 publications
5
53
0
Order By: Relevance
“…Overall prevalence of the present study is comparable with the results of most CT studies: 42.5 [5], 41.7 [6]. and 39% [7], One study [8] mentions quite different results: overall prevalence of 27%, maxillary involvement of only 8% with no polyps seen on any scan. For this latter study, it has to be noted that the maxillary sinuses were only seen in 38 out of 100 patients.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Overall prevalence of the present study is comparable with the results of most CT studies: 42.5 [5], 41.7 [6]. and 39% [7], One study [8] mentions quite different results: overall prevalence of 27%, maxillary involvement of only 8% with no polyps seen on any scan. For this latter study, it has to be noted that the maxillary sinuses were only seen in 38 out of 100 patients.…”
Section: Discussionsupporting
confidence: 79%
“…However, most CT studies in asymp tomatic populations show the ethmoidal rather than the maxillary sinuses as the first site of involvement: 28.4 and 24.8%, respectively [5], 28 and 18% [7], 21 and 8% [8], Only one CT study confirms the highest prevalence rate at the level of the maxillary rather than the anterior ethmoi dal sinuses: 27.8 and 19.4% [6]. Perhaps some of the more minor maxillary mucosal changes remain undetected on CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that otolaryngologists diagnosed sinus disease at a lower rate than the CT scan, alone, supports previous research showing that not all abnormalities found on CT scans indicate rhinosinusitis [10][11][12] . This finding supports the need for expert clinical evaluation.…”
Section: Discussionsupporting
confidence: 75%
“…Correlation of plain films with CT scans to evaluate mucosal thickening or opacification occurs in only 40% [10]. Similarly, negative plain films correlate with CT scanning in only about 10% [11]. Because the sensitivity and specificity occurs in such low percentages, plain films are not recommended for routine use in evaluating chronic rhinosinusitis.…”
Section: Imagingmentioning
confidence: 93%